2009
DOI: 10.1017/s1041610209991141
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of the Clock Drawing Test compared to that of standard screening tests for Alzheimer's disease: results from a study of Brazilian elderly with heterogeneous educational backgrounds

Abstract: Background: Although the Clock Drawing Test (CDT) is the second most used test in the world for the screening of dementia, there is still debate over its sensitivity, specificity, application and interpretation in dementia diagnosis. This study has three main aims: to evaluate the sensitivity and specificity of the CDT in a sample composed of older adults with Alzheimer's disease (AD) and normal controls; to compare CDT accuracy to the that of the Mini-mental State Examination (MMSE) and the Cambridge Cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 37 publications
2
76
0
12
Order By: Relevance
“…Although educa tion entered as a covariate on the ordinal linear regression models, the low variance between the groups (not signifi cant) may reduce its influence on test performance. Although some studies reported good criterion validity for the CDT among poorly educated older adults 8,10,11 , these findings are controversial 3,9 . Concerning construct validity, for patients with very low formal education, the drawing processes may demand, besides more cognitive effort than better educated subjects, the recruitment of different cognitive abilities to im prove task performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although educa tion entered as a covariate on the ordinal linear regression models, the low variance between the groups (not signifi cant) may reduce its influence on test performance. Although some studies reported good criterion validity for the CDT among poorly educated older adults 8,10,11 , these findings are controversial 3,9 . Concerning construct validity, for patients with very low formal education, the drawing processes may demand, besides more cognitive effort than better educated subjects, the recruitment of different cognitive abilities to im prove task performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it showed good evi dence of reliability, but reduced criterion-related validity for this population 9 . Other studies 10,11 , however, assessed CDT validity for cognitive assessment among individuals with heterogeneous educational backgrounds, including illitera cy, showing good results, but emphasizing the role of formal edu cation on test performance.…”
mentioning
confidence: 99%
“…Diversos estudios han mostrado correlación de la PDR con otras pruebas de detección de demencia, incluido el MMSE (21,35,36) . En la presente investigación se obtuvo un resultado similar al analizar la sensibilidad y especificidad de la PDR-M y el MMSE; obteniendo áreas bajo la curva ROC similares.…”
Section: Discussionunclassified
“…[21][22][23][24][25][26][27][28][29]. The neuropsychological test battery included the Boston Naming Test (BNT) [21], Rey Auditory Verbal Learning Test (RAVLT5 -sum of 5 recall trials of 15 words, RAVLT6 -immediate recall after inference and RAVLT7 -delayed recall after 30 minutes) [25], the Rey-Osterrieth Complex Figure Test copy and delayed recall (REY-C and REY-30) [26], Semantic Verbal Fluency animal category (VF) [22], Phonological Verbal Fluency (FAS), [24] Forward and Backward Digit Span Test (FDST and BDST) [29], Trail Making Test part A and B (TMT-A and TMT-B) [23], Clock Drawing Test (CDT) [27], and Digit Symbols Substitution Test (DSST) [28].…”
Section: Neuropsychological Evaluation (Npe)mentioning
confidence: 99%